Family Quality of Life: Perspectives of Family Caregivers of People with Dementia. (3rd April 2019) - Samuel, Preethy S.; DiZazzo-Miller, Rosanne
Abstract: Aims: Most caregiving literature focuses on individual-level outcomes, with sparse knowledge on family-level outcomes. Therefore, the purpose of this study was to describe the family quality of life (FQOL) of people with dementia and identify factors that influence their FQOL, as perceived by family caregivers. Methods: A convenience sample of 31 family caregivers of people with dementia was interviewed using a modified version of the Family Quality of Life Survey (FQOLS-2006). Statistical analyses were conducted to examine domain level and global FQOL outcomes. Results: Although caregivers reported the highest level of attainment in the domain of family health, they were also least satisfied with this domain. Global FQOL was significantly associated with caregiver health, care-recipient co-morbidities of psychological and motor problems, and three (health, leisure, community) of the nine FQOL domain level outcomes. Conclusion: Encouraging families to increase leisure participation can improve their health and global FQOL.